Хлеба и чуда: сборник / Ариадна Борисова - Борисова Ариадна Валентиновна (За чужими окнами, 2016)
Экземпляры: ф.6 (20170920) / Инвентарный номер: 54219 / Цена: / Сис.шифр: Р2 / Авт.знак: Б 82 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6-44